Case Report: Secondary Syphilis And Human Immunodeficiency Virus Coinfection - Lita Setyowatie; Adya Sitaresmi (Asian Journal of Health Research, 2022)
Introduction: Syphilis is a sexually transmitted infection that is chronically progressive, with a broad spectrum of active clinical and asymptomatic periods. A total of 80.6% of men with syphilis were Men Who Sex with Men (MSM), 47% of the population was coinfected with Human Immunodeficiency Virus (HIV). Case Presentation: Male, 23-yo, MSM, unmarried, HIV, complaining of red bumps and spots on the palms, soles, and upper arms since 4 days ago. One week earlier, he complained of sores in the genitals, which recurred 1 year ago and healed on their own. Dermatological examination revealed multiple erythematous patches and papules. The corpus penis, glans penis, and scrotum showed erosions and multiple ulcers with an erythematous-based, covered with yellowish crusts. VDRL and TPHA were reactive. The patient was diagnosed with secondary syphilis and treated with an intramuscular injection of benzathine penicillin 2.4 million IU once. A 1-month evaluation showed significant lesion improvement, VDRL titer 1:64. Evaluation of the 3rd and 6th months revealed a VDRL titer of 1:4. Conclusion: The clinical manifestations of syphilis patients with HIV coinfection are generally more atypical, aggressive, and overlap caused by changes in the immune system in HIV infection. Unsafe sexual behavior in MSM increases the transmission of syphilis infection. Diagnosis and therapy are generally the same. Men Who Sex with Men is a factor that allows the transmission of syphilis in HIV patients. Administration of benzathine penicillin injection once gave lesion improvement and significantly reduced VDRL.